Design do vestuário infantil: as texturas como experiência tátil para crianças deficientes visuais - Bononi, Juliana [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The main purpose of this work is to verify how the design is assisting in the development of products for children's clothing that provide tactile experiences for children with visual impairment. Since the quality of tactile stimulation for children is a fundamental importance, and that the clothing may be considered educational, as well as textures can be used as a learning resource, because reflect in the development of perception and interpretation through sensory exploration, are these resources being used to help children with Visual Impairment? These issues were addressed through a bibliographical study, which included the design issues, child development and visual impairment. As well as questionnaires, interviews and usability tests have assessed the child's relationship with the clothing and the mentioned tactile experience. It was observed that the designers have favored both the colors and prints, in other words the visual texture, as well as tactile textures and accessories in the pieces of children's clothing. We tried to see how these elements provide tactile experiences for these children, and if these users and their trainers - parents and teachers - explore such possibilities stimulus in their day by day. It was concluded that the tested clothing is efficient, since it has a large number of tactile elements, but the lack of stimuli from educators and parents who do not realize the potential of tactile experience through clothing, affects efficacy of this type of product.

O principal objetivo desse trabalho é verificar de que forma o design está auxiliando no desenvolvimento de produtos para o vestuário infantil que ofereçam experiências táteis para crianças com deficiência visual. Visto que a qualidade do estimulo tátil para as crianças é de fundamental importância, e que o vestuário pode ser considerado pedagógico, assim como as texturas podem ser usadas como recurso de aprendizagem, pois refletem no desenvolvimento da percepção e interpretação por meio da exploração sensorial, será que esses recursos estão sendo utilizados para auxiliar as crianças com Deficiência Visual? Estas questões foram abordadas através de estudo bibliográfico que englobou os temas design, desenvolvimento infantil e deficiência visual. Assim como, questionários, entrevistas e testes de usabilidade procuraram verificar as relações da criança com o vestuário e a experiência tátil citada. Observou-se que os designers têm privilegiado tanto as cores e estampas, ou seja, a textura visual, como também texturas táteis e acessórios nas peças do vestuário infantil. Procurou-se verificar de que forma esses elementos oferecem experiências táteis para essas crianças, bem como se estes usuários e seus formadores – pais e professores - exploram tais possibilidades de estímulo no seu dia a dia. Concluiu-se que o vestuário testado é eficiente, visto que possui um grande número de elementos táteis, porém a falta de estímulos por parte dos educadores e dos pais, os quais não se apercebem do potencial da experiência tátil por meio do vestuário, afeta a eficácia deste tipo de produto.
Design of children's clothing: the textures and tactile experience for visually impaired children
Keywords: Inclusive design; Inclusive fashion; Visual impairment; Infant clothing; Tactile experience; Design Inclusivo; Moda Inclusiva; Deficiência Visual; Vestuário Infantil; Experiência Tátil